The Ribosome as a Switchboard for Bacterial Stress Response - Cheng-Guang, He; Gualerzi, Claudio Orlando (Frontiers in Microbiology, 2021)
As free-living organisms, bacteria are subject to continuous, numerous and occasionally drastic environmental changes to which they respond with various types of mechanisms which enable them to adapt to the new conditions so as to survive. Here we describe three situations in which the ribosome and its functions represent the sensor or the target of the stress and play a key role in the subsequent cellular response. The three stress conditions which are described are those ensuing upon: a) zinc starvation; b) nutritional deprivation and c) temperature downshift.